A formação continuada de professores de um Centro Integrado de Educação de Jovens e Adultos (CIEJA): referências freireanas - Machado, Adriana Silva (2021)
This research aimed to identify the contributions and limits of the continuing education courses held at an Integrated Center for Youth and Adult Education (Cieja) and its implications for the pedagogical practice of Youth and Adult Education teachers. The theoretical framework used was Paulo Freire's pedagogy and the writings of authors who are aligned with Freire's thought in relation to teacher education: Zeichner (1993), Nóvoa (1992), Imbernón (2009, 2011, 2016) André (2010, 2016), Saul (1998) and Saul and Saul (2017, 2018). The research context was a Cieja located in the city of São Paulo and the subjects were the teachers and the pedagogical coordinator who work at this Center. The research methodology had a qualitative approach and the procedures used for data collection were a questionnaire and a semi-structured interview. The subjects' answers were analyzed according to Bardin (2016) technique. The data produced in the research were systematized according to the categories of the theoretical framework, expressed in the Freirean conceptual plot focused on permanent education, as proposed by Paulo Freire. The research findings made possible to identify that the education at Cieja Campo Limpo works from Freirean theoretical-methodological assumptions, having as its starting point the dialogue and unveiling of reality, promoting discussions and critical reflections, denouncing inequalities, oppression, injustices, dehumanization and announcing the possibility of social change and transformation. It was concluded that the formations developed in this Cieja bring deep discussions about the theoretical and methodological processes of youth, adult and elderly literacy. However, the teachers of specific disciplines pointed out the need to deepen the contents and methods of literacy in order to improve their practices in this teaching modality